2000
DOI: 10.4049/jimmunol.165.11.6644
|View full text |Cite
|
Sign up to set email alerts
|

A Shift in the Phenotype of Melan-A-Specific CTL Identifies Melanoma Patients with an Active Tumor-Specific Immune Response

Abstract: In a significant proportion of melanoma patients, CTL specific for the melan-A26/7–35 epitope can be detected in peripheral blood using HLA-A2/peptide tetramers. However, the functional capacity of these CTL has been controversial, since although they prove to be effective killers after in vitro expansion, in some patients they have blunted activation responses ex vivo. We used phenotypic markers to characterize melan-A tetramer+ cells in both normal individuals and melanoma patients, and correlated these mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 38 publications
9
117
0
1
Order By: Relevance
“…By complementing the use of A2/Melan-A tetramers with both intracellular perforin staining and surface staining of memory/naivety markers, we found that the percentages of activated cells were also comparable. These observations are in agreement with previous literature data indicating that Melan-A-specific CTL from both melanoma and vitiligo patients frequently show signs of an in vivo antigen encounter [13,14,25,26], and indicate that the activation status of melanocyte-specific CTL is not a distinctive feature of either disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By complementing the use of A2/Melan-A tetramers with both intracellular perforin staining and surface staining of memory/naivety markers, we found that the percentages of activated cells were also comparable. These observations are in agreement with previous literature data indicating that Melan-A-specific CTL from both melanoma and vitiligo patients frequently show signs of an in vivo antigen encounter [13,14,25,26], and indicate that the activation status of melanocyte-specific CTL is not a distinctive feature of either disease.…”
Section: Discussionsupporting
confidence: 93%
“…Second, we evaluated the response to the melanoma target in terms of TCR down-regulation. For this experiment, we chose the only melanoma patient whose PHA line exhibited some degree of TCR downregulation versus the natural Melan-A [26][27][28][29][30][31][32][33][34][35] peptide, a prerequisite for melanoma cell recognition, and we selected the vitiligo patient exhibiting the most similar behavior. The results indicated that only vitiligo CTL were capable of TCR down-regulation in response to this stimulus (Fig.…”
Section: Tumor Reactivity Of Whole Melan-a-specific Cytotoxic T Lymphmentioning
confidence: 99%
“…To ensure that this technique could be applied to the enrichment of such a T cell population, we used Melan-A-specific T cells. Phenotypic [12], functional [13] and molecular techniques [14] have confirmed unequivocally that in normal individuals, these T cells are truly antigen naive. Following enrichment, Melan-Aspecific T cells could be found at a frequency of 83.78% of CD8 + T cells (Fig.…”
Section: Magnetic Selection Of Naive Populations Of Melan-a-specific mentioning
confidence: 85%
“…T cells producing Th1 cytokines (IFNg and IL-2) have been shown to be responsible for antitumor reactivity. [33][34][35] Previously, we showed that HA-2-specific T cells isolated by tetramer during a strong GVL response produced large amounts of IFNg and no or low amounts of IL-4. 18 Furthermore, we recently demonstrated that T cells contributing to the GVL reactivity of DLI can be isolated based on their production of IFNg.…”
Section: Discussionmentioning
confidence: 99%